A Conserved cis-Regulatory Module Determines Germline Fate through Activation of the Transcription Factor DUO1 Promoter. Issue 1 (13th September 2016) - Peters, Benjamin; Casey, Jonathan; Aidley, Jack; Zohrab, Stuart; Borg, Michael; Twell, David; Brownfield, Lynette
Abstract : A cis-regulatory module conserved in eudicots directs spatial and temporal control of the transcription factor DUO1 to specify male germline fate. Abstract: The development of the male germline within pollen relies upon the activation of numerous target genes by the transcription factor DUO POLLEN1 (DUO1). The expression of DUO1 is restricted to the male germline and is first detected shortly after the asymmetric division that segregates the germ cell lineage. Transcriptional regulation is critical in controlling DUO1 expression, since transcriptional and translational fusions show similar expression patterns. Here, we identify key promoter sequences required for the germline-specific regulation of DUO1 transcription. Combining promoter deletion analyses with phylogenetic footprinting in eudicots and in Arabidopsis accessions, we identify a cis-regulatory module, Regulatory region of DUO1 ( ROD1 ), which replicates the expression pattern of DUO1 in Arabidopsis ( Arabidopsis thaliana ). We show that ROD1 from the legume Medicago truncatula directs male germline-specific expression in Arabidopsis, demonstrating conservation of DUO1 regulation among eudicots. ROD1 contains several short conserved cis-regulatory elements, including three copies of the motif DNGTGGV, required for germline expression and tandem repeats of the motif YAACYGY, which enhance DUO1 transcription in a positive feedback loop. We conclude that a cis-regulatory module conserved in eudicots directs the spatial and temporal expression of the transcription factor DUO1 to specify male germline fate and sperm cell differentiation.